Islamic Educational Thought of Ibn Jama'ah : Critical Analysis of Teaching and Learning Objectives - Muhammad Hamzah; Sakdiah; Sri Astuti; Muhammad Furqan (State Islamic Institute of Madura, 2022)
Research on the thoughts of one of the figures of Islamic education with his work Tadzkiratus Sami wa al-Mutakallim fi Adabil Ilmi wa al-Mutakallim named Ibn Jama'ah, aims to find out the relevance of his thinking in the modern era related to the purpose of teaching and learning. Using library research, descriptive analysis through assessment from several literature reviews and from various other relevant sources, a thorough and in-depth picture of adab-adab or ethical procedures will be obtained to achieve teaching and learning goals as expected. Our findings suggest that there has been a decline in morale today as a result of the impact of modernization due to the lack of religious science education and moral education in learners. Ibn Jama'ah's thoughts regarding the purpose of teaching and learning are still relevant and feasible to be applied today.